2016
DOI: 10.1007/s13300-016-0203-x
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence Contributes to an Improved Quality of Life in Type 2 Diabetes Mellitus Patients: A Cross-Sectional Study

Abstract: IntroductionDiabetes mellitus is a chronic disease with a high prevalence world wide. This disease has also been reported to affect the quality of life (QOL) of the patient and their family due to its chronic nature and multi organ involvement. The aim of this study was to analyze the association between adherence to prescribed diabetes medication and diabetes-specific QOL in patients attending Secondary Health Care Facility in Bandung City, Indonesia.MethodsA cross-sectional survey was conducted in the Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 34 publications
5
49
1
5
Order By: Relevance
“…However, the findings remain controversial. Consistent with our findings, several studies have previously demonstrated the beneficial effects of medication adherence on improved QoL in epileptic patients [10,44,45] and other diseases [46,47]. Loon et al [47] found that adherence to glaucoma medications was associated with better QoL.…”
Section: Discussionsupporting
confidence: 92%
“…However, the findings remain controversial. Consistent with our findings, several studies have previously demonstrated the beneficial effects of medication adherence on improved QoL in epileptic patients [10,44,45] and other diseases [46,47]. Loon et al [47] found that adherence to glaucoma medications was associated with better QoL.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, due to chronic nature of the disease, the likelihood of non-adherence is expected [23]. Adherence to the prescribed medication was positively linked with diabetes-specific -quality of life in patients [24].…”
Section: Disscussion Adherence To Medicationmentioning
confidence: 99%
“…The BIPQ assesses eight dimensions, i.e., consequences, timeline, personal control, treatment control, identity, concern, coherence and emotional response. The higher score of BIPQ domains, the more negative perception of patients (question number 1, 2, 5,6,8). On the other dimensions (i.e., personal control, treatment control and coherence) the higher the score, the more positive the perceptions of the patients are (number 3, 4, and 7).…”
Section: Methodsmentioning
confidence: 99%